Integrating Curriculum Development, Teaching Strategies, and Assessment in Education - Siti Nur Avira; Nur Zalfah Nabila M (Journal of Strategy and Transformation in Educational Management, 2026)
Education in the 21st century requires an integrated approach that aligns curriculum development, instructional strategies, and assessment practices to ensure meaningful learning outcomes. Many educational systems still treat these three components separately, leading to fragmented learning experiences and inconsistent evaluation of student achievement. This paper examines the relationship between curriculum development, teaching strategies, and assessment in contemporary education and argues that their integration is essential for improving educational quality. Using a conceptual and literature-based approach, this study synthesizes theories and empirical findings from curriculum studies, instructional design, and educational assessment. The analysis demonstrates that an aligned educational system enhances student engagement, deepens understanding, and supports fair and authentic evaluation of learning. The paper concludes that policymakers, educators, and institutions must adopt a holistic framework that connects curriculum planning, classroom practice, and assessment to foster more effective and equitable education.